1991
DOI: 10.1200/jco.1991.9.8.1462
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of unilateral adrenal masses in patients with operable non-small-cell lung cancer.

Abstract: Although adrenal metastases are frequently noted with non-small-cell lung cancer (NSCLC) at autopsy, their incidence in patients with operable NSCLC is unclear. We prospectively assessed consecutive patients with otherwise operable NSCLC for the incidence and histology of unilateral adrenal masses. Assessment included blood chemistries, lung function tests, bronchoscopy, chest x-ray, bone scan, and computed tomography (CT) of the head, chest, and upper abdomen. Of 246 patients with otherwise operable NSCLC, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 0 publications
0
73
0
6
Order By: Relevance
“…10 -12,25 In patients who are evaluated for staging of operable nonsmall cell lung carcinoma accompanied by adrenal gland enlargement, a nondiagnostic FNA sample may have far-reaching implications, including the possible recommendation of adrenalectomy. 26 In addition to the experience of the operator, another possible explanation for the increased sample yield in the current study is that a cytopathologist always was present on-site for the assessment of sample adequacy. Like us, Fassina et al, 10 in their study of image-guided FNA biopsy of the adrenal gland, suggested that the increased specimen adequacy rate observed (108 of 119 [91%]) could be attributed to the presence of a cytopathologist whose duty was to assess specimen adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…10 -12,25 In patients who are evaluated for staging of operable nonsmall cell lung carcinoma accompanied by adrenal gland enlargement, a nondiagnostic FNA sample may have far-reaching implications, including the possible recommendation of adrenalectomy. 26 In addition to the experience of the operator, another possible explanation for the increased sample yield in the current study is that a cytopathologist always was present on-site for the assessment of sample adequacy. Like us, Fassina et al, 10 in their study of image-guided FNA biopsy of the adrenal gland, suggested that the increased specimen adequacy rate observed (108 of 119 [91%]) could be attributed to the presence of a cytopathologist whose duty was to assess specimen adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…The ®nding of an isolated adrenal mass on CT is often a diagnostic challenge. About two-thirds of cases could be explained by an asymptomatic adrenal adenoma in some series [110,113]. An adrenal mass, therefore does not imply inoperable disease, but rather the need for further (pathological) examination by, for example, puncture or biopsy of the lesion [113].…”
Section: Extrathoracic Staging (M Status)mentioning
confidence: 99%
“…46,47 Historically, the MS of patients with an AM, in whom it and the primary are left in situ, is 9 months. 22 Five-year OS is essentially zero in the absence of an actionable molecular mutation. 4 There is no randomized evidence supporting the use of any AM-directed therapy, and no prospective studies directly comparing surgery and SBRT.…”
Section: Discussionmentioning
confidence: 99%